Printing and prophecy: prognostication and media change, 1450 - 1550 - Green, Jonathan (Cultures of knowledge in the early modern world, 2012)
Introduction: printing and prophecy -- The Sibyl's book -- Prophets in print -- Prophets and their readers -- Visions of visions: functions of the image in printed prophecy -- Practica teütsch -- Fear, floods, and the paradox of the practica teütsch -- Conclusion: the prophetic reader